EFFECT OF SOURSOP LEAF (Annona muricata) EXTRACT AS LARVACIDE AGAINST INSTAR III Aedes aegypti LARVAE - Sri Puji Hartini; Betta Kurniawan; Syazili Mustofa; Endah Setyaningrum (Fakultas Kedokteran Universitas Lampung, 2014)
Background: Dengue hemorrhagic fever (DHF) is an endemic disease in Southeast Asia, including Indonesia. The use of insecticide induce negative impact, so it required natural ingridients like soursop leaf (Annona muricata). The research was conducted to perceive the effectiveness of soursop leaf extract as larvacide, LC50 and LT50 values.Method: The research design is an experimental, using completely randomized design. The amount of sample used was 480 larvas, which divided into 6 groups of soursop leaf extract concentration, 0% (negative control); 0,25%; 0,5%; 0,75%; 1%; and abate 1% (positive control). Each container contained 20 larvas and was given 200 ml soursop extract solution, repeated for 4 times. Kruskal-wallis test (p<0.05), Post-Hoctest Mann-Whitney (p<0.05) and Probit analized is used to analize LC50 and LT50 value.Result: The research showed that the amount of dead larvae was 28,75% at a concentration of 0,25%; 58,75% at a concentration of 0,5%; 95% at a concentration of 0,75%; and 96,25% at a concentration of 1%. The effective concentration were 0,75% and 1% because the larvacide potency is almost equal as abate 1%. LC50value was 0,989% at at 20th minute; 0,897% at 40th minute; 0,777% at 60th minute; 0,349% at 120th minute; 0,220% at 240th minute; 0,207% at 480th minute; 0,165% at 1.440th minute; 0,110% at 2.880th minute and 0,087% at 4.320th minute. LT50 value was 1528,747 minutes at concentration of 0,5%; 148,688 minutes at a concentration of 0,75% and 106,650 minutes at a concentration of 1%.Conclusion: Soursop leaf (Annona muricata) extract has larvacide effect against instar III Aedes aegypti larvae. [J Agromed Unila 2014; 1(1):8-15] Keywords: aedes aegypty, annona muricata, larvacide